Turkish World and Literary Relations of the East - Minnegalieva, Aigul Ildusovna; Mingazova, Liailia Ihsanovna; Ibrayeva, Aigerim Tarbinovna; Kayumova, Gelyusya Faridovna (International Journal of Criminology and Sociology, 2022)
All Turkic literature has a common cultural framework. A substantial confirmation of this fact comes from the national spiritual heritage, which has become the basis for the further development and flourishing of the verbal art of Turkic peoples. First of all, these are Китабы Деде Коркут of the Oghuz, the Kyrgyz heroic epos Манас (Manas), Идегей (Idegei) – the variants of which were widespread among the Kazakhs and the Tatars, the famous Чура батыр (Chura Batyr) among the Tatars, etc. The works such as A Thousand Nights and a Night (Мың бір түн), Shakhname or Shakh-Name (Шахнама), Kalila and Dimna (Кәлила мен Димна), Leili and Majnun (Ләйлі-Мәжнүн), Zhusip-Zylikha (Жүсіп-Зылиха), Takhir-Zukhra, Farkhad-Shyryn or Khosrov-Shyryn (Хұсрау-Шырын) have exerted a significant influence on the development of literature. The article concludes that, despite the national differences of the Turkic peoples, they are united by common literary background, common goals, and interests, moral, spiritual, and cultural values. It is proved out again that the literature of the Turkic peoples is abundant in authors and works, characterized by a variety of genres and poetic forms, ideological and thematic wealth, and a high artistic level. Emphasis is also put on the fact that in the eastern tradition, there are many samples of word-of-mouth literature of the general plot and cultural heritage of the Turkic peoples who had inhabited the eastern lands since ancient centuries.